Systematic Literature Review : Dinamika Strategi Guru dalam Mengontrol Emosi Anak ADHD di SLB PGRI Kamal (International Forum of Researchers and Lecturers, 2025)
This study aims to identify teacher strategies in regulating the emotions of children with moderate Attention Deficit Hyperactivity Disorder (ADHD) at SLB PGRI Kamal. Using the Systematic Literature Review (SLR) method with the PICO (Population, Intervention, Comparison, Outcome) approach, it was found that teacher strategies include firm verbal communication, light physical touch such as patting the shoulder, short and clear instructions, short study sessions with breaks, and diversion through light tasks. This strategy has been proven effective in reducing emotional outbursts and increasing children's focus in class. The success of implementing the strategy is highly dependent on teacher readiness, collaboration with parents, and support from the school environment.